The Effects of Long-Term Operation and High Temperature on Material Properties of Austenitic Stainless Steel Type 321H - Al-Khazraji, Ahmed Naif; Amin, Samir Ali; Al-Warmizyari, Husam Ahmed (Al-Khwarizmi Engineering Journal, 2017)
Changes in mechanical properties of material as a result of service in different conditions can be provided by mechanical testing to assist the estimation of current internal situation of these materials, or the degree of deterioration may exist in furnaces serviced at high temperature and exceed their design life. Because of the rarity works on austenitic stainless steel material type AISI 321H, in this work, ultimate tensile strength, yield strength, elongation, hardness, and absorbed energy by impact are evaluated based on experimental data obtained from mechanical testing. Samples of tubes are extracted from furnace belong to hydrotreaterunit, also samples from un-used tube material are used to make comparisons between these properties. Tensile properties of stainless steel (AISI 321H) were decreased as temperature increases; the trend of properties decreasing for the samples of un-used tube material is the same for the ex-used material. The trend of stress-strain curve will not change due to elevated temperature exposure for long time of service, except the yield strength will be higher in this diagram. The yield strength increased under these conditions, but the ability of material which is elongated will decrease. Hardness and absorbed energy increased by 11.28 and 14% respectively when the material is aged for long time under effect of high temperature accompanied with creep effect. Keywords: Hardness, Impact, Mechanical Properties, Stainless Steel 321H, Mechanical Properties, Tensile Strength, Tube Furnace.